EVALUASI PROGRAM PELATIHAN PENGOLAHAN BAHAN PUSTAKA DI PUSDIKLAT PERPUSTAKAAN NASIONAL RI - Muhammad Fadhil; Dr. Neti Karnati, M. Pd; Dr. Matin, M. Pd (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2020)
This research was intended to see how the Kirkpatrick four level evaluation model is applied in the Library Material Processing training program organized by the Education and Training center of National Library of Indonesia. This evaluation research uses the Kirkpatrick evaluation model (Reaction, Learning, Behavior, Result). The subject of this research is training organizers, training instructors and training participants in the processing of library materials. Data collection techniques in this study used observation, documentation and interviews. Data validity test is done using triangulation of sources and methods. The results of this study show that the implementation of the Library Material Processing Training program has not gone well based on the aspect that being evaluated. 1) In the Reaction evaluation aspect, the implementation of training at this stage goes well. It can be seen from the results of the evaluator's last evaluation score which has a score of 93.88 or very satisfied and the last evaluation score of the instructor who has a score of 90.66 or very satisfied. 2) In the aspect of learning evaluation, the training process goes well according to the plan that was made before. This can be seen from the final score of all participants who have a score above the least limit. 3) in the Behavior aspect, the training organizers have not carried out observations of the participants' behavior after the training. 4) Then in the Result aspect, the training organizers also have not carried out observations on the participants' contributions or the use of participant's knowledge of the library performance.